Activation of EHF via STAT3 phosphorylation by LMP2A in Epstein‐Barr virus–positive gastric cancer. Issue 8 (13th June 2021) - Li, Wenzhe; Okabe, Atsushi; Usui, Genki; Fukuyo, Masaki; Matsusaka, Keisuke; Rahmutulla, Bahityar; Mano, Yasunobu; Hoshii, Takayuki; Funata, Sayaka; Hiura, Nobuhiro; Fukayama, Masashi; Tan, Patrick; et al.
Abstract: Epstein‐Barr virus (EBV) is associated with approximately 10% of gastric cancers (GCs). We previously showed that EBV infection of gastric epithelial cells induces aberrant DNA methylation in promoter regions, which causes silencing of critical tumor suppressor genes. Here, we analyzed gene expressions and active histone modifications (H3K4me3, H3K4me1, and H3K27ac) genome‐widely in EBV‐positive GC cell lines and in vitro EBV‐infected GC cell lines to elucidate the transcription factors contributing to tumorigenesis through enhancer activation. Genes associated with "signaling of WNT in cancer" were significantly enriched in EBV‐positive GC, showing increased active β‐catenin staining. Genes neighboring activated enhancers were significantly upregulated, and EHF motif was significantly enriched in these active enhancers. Higher expression of EHF in clinical EBV‐positive GC compared with normal tissue and EBV‐negative GC was confirmed by RNA‐seq using The Cancer Genome Atlas cohort, and by immunostaining using our cohort. EHF knockdown markedly inhibited cell proliferation. Moreover, there was significant enrichment of critical cancer pathway–related genes (eg, FZD5 ) in the downstream of EHF. EBV protein LMP2A caused upregulation of EHF via phosphorylation of STAT3. STAT3 knockdown was shown to inhibit cellular growth of EBV‐positive GC cells, and the inhibition was rescued by EHF overexpression. Our data highlighted the important role of EBV infection in gastric tumorigenesis via enhancer activation. Abstract : We here analyzed the global alteration of gene expressions and active histone modifications to identify activated enhancer regions after EBV infection and to predict the master transcription factors in EBV‐positive GC. We identified that EHF was a critical transcription factor at active enhancers, which promoted cell proliferation in EBV‐positive GC. In addition, we identified its downstream target gene, FZD5, which is a potential oncogene that regulates cell growth after EBV infection.